Pendampingan Optimalisasi Mini Bank FEBI Universitas Islam Negeri Syekh Wasil Kediri sebagai Income Generating Unit melalui Program Intership, Partnership, dan Empowering - Ghofur, Abdul; Karem, Nahdya Alfaina; Muzakky, Ahmad Ilham Syiham; Andriani, Andriani (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
The mini bank laboratory is a good initiative for student empowerment, aimed at providing a deeper understanding of banking products and services, as well as effective and efficient financial management. The mini bank laboratory at FEBI UIN Syekh Wasil Kediri serves as a platform for students to develop their potential and actualize their skills in managing Islamic financial institutions. Through practical training and hands-on experience, the FEBI UIN Syekh Wasil Kediri mini bank laboratory is expected to produce a skilled and ready workforce to meet the challenges of the ever-evolving banking industry.The FEBI UIN Syekh Wasil Mini Bank has implemented several programs including internships, partnerships, and empowerment initiatives, but it has not yet become a unit that generates income for the faculty or the university. The purpose of this study is to provide assistance in optimizing the internship, partnership, and empowerment programs so that the mini bank can serve as an income-generating unit.The approach method used is service learning, a learning method that combines academic learning with real-life experiences in service and development within the mini bank laboratory. The targets of this program optimization include generating income for the university, providing efficient and affordable services, serving as a practical learning environment, and developing Islamic financial products.The outcomes of this program include improved quality among internship participants, increased participants in the BSI application as a partnership platform, and a rise in beneficiaries of the empowerment program. However, the mini bank has not yet succeeded in generating income for the faculty or the university.